Crafting digital writing : composing texts across media and genres - Hicks, Troy (Heinemann, 2013)
Introduction -- Author's craft, genre study, and digital writing -- Crafting web texts -- Crafting presentations -- Crafting audio texts -- Crafting video texts -- Crafting social media -- Modeling and mentoring the digital writing process.